Effects of imagery and mindfulness on anxiety, confidence, mental well-being, and performance in shot putt throwers: A case study - Deck, S.; Kouali, D.; Hall, C. (Journal of Emerging Sport Studies, 2018)
The purpose of the present study was to introduce imagery and mindfulness to athletes as tools to help deal with competition anxiety, and improve confidence, mental well-being, and performance. Two female varsity level throwers (Mage = 20) met individually with the researcher twice a week during the competitive season (25 weeks). Athletes were introduced to breathing and relaxation techniques, followed by basic imagery scripts and mindfulness. Results revealed that both athletes decreased their anxiety levels, while increasing their self-confidence, mental well-being, and performance. The findings highlight the positive effect of employing a combination of imagery and mindfulness in sport life.